2001
DOI: 10.1006/dbio.2001.0480
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ2 in Corneal Morphogenesis during Mouse Embryonic Development

Abstract: To examine the roles of TGFbeta isoforms on corneal morphogenesis, the eyes of mice that lack TGFbetas were analyzed at different developmental stages for cell proliferation, migration and apoptosis, and for expression patterns of keratin 12, lumican, keratocan and collagen I. Among the three Tgfb(-/-) mice, only Tgfb2(-/-) mice have abnormal ocular morphogenesis characterized by thin corneal stroma, absence of corneal endothelium, fusion of cornea to lens (a Peters'-like anomaly phenotype), and accumulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
132
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 156 publications
(138 citation statements)
references
References 46 publications
5
132
0
1
Order By: Relevance
“…The tight correlation between shape changes, cytoskeletal remodeling, and cilia assembly and disassembly in CECs during postnatal development led us to hypothesize that the cilium of CECs controls CE patterning. Null mutations that completely abolish cilia lead to midgestation lethality, before the CE layer is established (22). The IFT88 protein is a component of the IFT, the bidirectional movement of particles between the tip and the base of the cilium required for cilia assembly and maintenance first described in Chlamydomonas (23).…”
Section: Resultsmentioning
confidence: 99%
“…The tight correlation between shape changes, cytoskeletal remodeling, and cilia assembly and disassembly in CECs during postnatal development led us to hypothesize that the cilium of CECs controls CE patterning. Null mutations that completely abolish cilia lead to midgestation lethality, before the CE layer is established (22). The IFT88 protein is a component of the IFT, the bidirectional movement of particles between the tip and the base of the cilium required for cilia assembly and maintenance first described in Chlamydomonas (23).…”
Section: Resultsmentioning
confidence: 99%
“…Although a mouse embryo that lacks TGFb1 or TGFb3 does not have any ocular abnormalities, a mouse embryo lacking TGFb2 has multiple defects in ocular structures, that is, thin cornea with a loss of the corneal endothelium and anterior chamber, immature retina, and persistent vitreous vessels. [44][45][46][47][48] These findings may coincide with the fact that TGFb2 predominates in eye aqueous humor. Overexpression of TGFb1 by using a-crystalline promoter in TGFb2-null mice rescues the abnormalities in ocular development caused by the deletion of TGFb2.…”
Section: Embryogenesis and Developmental Disordersmentioning
confidence: 99%
“…Our preliminary experiments showed that there was no obvious difference in the histology or healing at the macroscopic level of an alkali-burned mouse eye receiving either Cre-Ad or no application of adenovirus (no vector group), and thus we used corneas of Cre-Ad group as controls. After the evaluation of the corneal surface, the eye globe was enucleated 2 h after labeling with bromodeoxyuridine (BrdU) 40 and processed for histological examination in either paraffin sections or cryosections at Day 5, 10, and 20. The number of eyes for paraffin sections were 10 and 10 (Day 5), 9 and 12 (Day 10), or 12 and 12 (Day 20) in the Cre-Ad and BMP-7-Ad groups, respectively.…”
Section: Alkali Burn In C57bl/6 Mice and Its Treatment With Bmp-7 Genmentioning
confidence: 99%
“…Immunohistochemistry for TGF-b1-3 was performed as previously reported. 43,44 Cell proliferation in healing epithelium was determined by immunostaining with anti-BrdU antibody (1:11 in PBS, Roche Diagnostics, Mannheim, Germany) as previously reported 40 and by determining the number of labeled cells in whole healing epithelia in the affected cornea. Specimens were treated with 2 N HCl for 60 min at 371C prior to antibody application.…”
Section: Immunohistochemistrymentioning
confidence: 99%